Innovation in Technology, Financial Literacy, and Security Risk in Cardless Withdrawals: Case Study on Customers Adoption at Bank Syariah Indonesia - Henderianto, Ricky; Adinugraha, Hendri Hermawan; Shultoni, Muhammad; Andrean, Rizky (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2025)
Purpose: This study aims to analyze the impact of technological innovation, financial literacy, and security risk on the adoption of cardless withdrawal services among customers of Bank Syariah Indonesia (BSI) in Pekalongan Regency.Design/methodology: A quantitative research approach was employed, collecting data through a questionnaire distributed via Google Forms. The sample size was determined using the Lemeshow formula, resulting in 97 respondents. Data analysis included classical assumption tests, multiple linear regression, and hypothesis testing.Findings: The results indicate that technological innovation and security risk positively and significantly inthe fluence the adoption of cardless withdrawal services. Customers perceive security as a crucial factor in their decision to use this service. However, financial literacy does not significantly impact adoption, suggesting that customers’ financial knowledge does not play a major role in their willingness to utilize this feature.Practical implications: The findings provide valuable insights for Islamic banks to enhance digital banking adoption by improving technological infrastructure and security features. Additionally, efforts should be made to raise awareness about financial literacy to encourage broader acceptance of innovative banking services.Originality/Value: This study explores the adoption of cardless withdrawal services within the context of Islamic banking, particularly in a regional setting that has not been extensively studied. It offers a novel contribution by examining the interplay of technological innovation, financial literacy, and security risk in influencing customer behavior.